VoIP Integration for Mobile Ride-sharing Application - (:unkn) unknown (IEEE, 2017)
Dynamic car pooling or ride sharing applications have become viable due to the recent advancement on mobile Internet infrastructure, smart mobile devices and matching algorithms based on social media data. These applications bring together car owners and possible riders. It is important to enable communication between riders and drivers without revealing personal details to the other party. In this paper a VoIP solution is presented which provides a platform for a ride-sharing system to make voice calls between drivers and riders without revealing their telephone numbers.
Keywords: dynamic ride sharing; privacy in dynamic ride sharing; VoIP applications